Upaya Pencegahan Bullying melalui Kegiatan Sosialisasi pada Siswa Dasar di Desa Sungai Keranji - Zelandy Aulya Marthisza; Dwi Putri Musdansi; Elvina Afriadni; Muhammad Fais; Destri Adelia (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
Students' understanding of the forms, impacts, and prevention of bullying at State Elementary School 018 and Elementary School 014, Sungai Keranji Village, remains largely unknown, necessitating the implementation of anti-bullying outreach activities at State Elementary School 014, Sungai Keranji Village. This activity aims to increase students' knowledge and awareness of bullying as a preventative measure in creating a safe and comfortable school environment. The community service method used consists of three stages: preparation, implementation, and evaluation. The outreach activities were carried out through lectures, discussions, questions and answers, and the use of educational images and videos. Evaluation was conducted using a questionnaire with a four-level Likert scale given to 76 student participants. The evaluation results showed that the outreach activities obtained an average score of 84.21%. These results indicate that the outreach activities were able to increase students' understanding of bullying, types of bullying, the impacts of bullying, and prevention efforts, thereby creating a safe, comfortable, and child-friendly school environment.